Gynecological clinical case - Alves Silva, Daniela (2021)
Herein is reported the case of a child observed in the Emergency Department due to urinary retention, suprapubic pain, and dysuria. Urine culture was performed upon cystitis suspicion, which was positive for Escherichia Coli, and the patient was treated with amoxicillin and clavulanic acid. Three days later, the child was reevaluated for persistent urinary retention, fever, and vaginal bleeding. At gynecological examination, she had an imperforate hymen. Imaging evaluation was performed, revealing an abdominal mass, suggestive of piohematocolpos. The patient was submitted to surgical drainage, with complete condition resolution.